Management of type 2 diabetes mellitus: insights into prescribing trends - K. M., Prasanna Kumar; Ingole, Shahu; Tamboli, Tushar; Jain, Rishi (International Journal of Research in Medical Sciences, 2017)
Background: Recently, management of type 2 diabetes mellitus (T2DM) has changed with advent of novel agents like DPP4i, SGLT2i and GLP-1 agonist. Of these, DPP4i have emerged as promising agents as monotherapy and as an add-on to metformin for improved glycaemic control. This survey was planned to explore current prescribing trends of physicians of India for the management of T2DM. Methods: This was a prospective, cross sectional, questionnaire-based survey of physicians and endocrinologist across different geographic areas in India. A survey questionnaire consisting of 10 questions related to management of T2DM in real-world clinical settings was prepared, validated in a small group of physicians and then administered to physicians and endocrinologists. Results: Responses from 502 physicians were received. About 60% physicians prefer DPP4i as first add-on to metformin followed by sulfonylurea (SU) (30%). Amongst DPP4i, vildagliptin and sitagliptin were preferred by 48% and 28% physicians respectively as first add-on to metformin. For patients uncontrolled on metformin + SU therapy, 54 % physicians prefer DPP4i as second add-on. Vildagliptin is perceived to have the better efficacy and safety data, as suggested by 40% and 43% physicians respectively. Large number of physicians (48%) were hesitant to prescribe teneligliptin due to insufficient data. SGLT2 inhibitors are preferred as third add-on by 44% physicians. Conclusions: DPP4i are being increasingly preferred by physician as an add-on to metformin. Among DPP4i, the survey revealed that vildagliptin is the most preferred DPP4i as an add-on to metformin possibly owing to its established safety and efficacy data.